Across the Great Divide : (Island Press, 2001)
Across the Great Divide presents a thoughtful exploration of this new movement, bringing together writing, reporting, and analysis of collaborative conservation from those directly involved in developing and implementing the approach. Contributors examine: the failure of traditional policy approaches, recent economic and demographic changes that serve as a backdrop for the emergence of the movement, the merits of, and drawbacks to, collaborative decision-making, the challenges involved with integrating diverse voices and bringing all sectors of society into the movement.